The incidence of conditionally pathogenic mycobacteria in the northern Moravia region in 1978-1987 - Kaustová, J (Journal of hygiene, epidemiology, microbiology, and immunology, 1992)
The incidence of potential pathogenic mycobacteria (PPM) has been studied in the Northern Moravia since 1970. The present paper follows up a previous communication summing up the finding for the period 1970-1977 during which were isolated from 713 persons. In 1978-1987, 4,658 strains were isolated from 1,917 persons. The species most frequently isolated was M. gordonae. A significant increase was observed in the incidence of mycobacterioses due to M. kansasii, namely from 2.90/100,000 in 1970 to 17.70/100,000 in 1987 in the Karvina district, the centre of endemic area. PPM was isolated from 321 water samples.
Keywords: bakteriologické techniky; Bacteriological Techniques; Humans; Child; Incidence; lidé; atypické mykobakteriální infekce; netuberkulózní mykobakterie; Water Microbiology; mikrobiologie vody; dítě; incidence; Czechoslovakia; Mycobacterium Infections, Nontuberculous; Nontuberculous Mycobacteria; Československo